Rethinking the Mediating Mechanism: HRM Practices and Employee Well-being - Saragih, Susanti; Margaretha, Meily; Suhada, Namira (UI Scholars Hub, 2024)
The relationship between Human Resource Management (HRM) practices and employee well-being is complex and often contradictory. While HRM practices can enhance employee well-being through various mechanisms, they can also negatively impact well-being, especially in contexts of high-demand jobs. This study investigates the mediating roles of job crafting and work engagement in this relationship. Data from 100 hotel employees in Bandung, Indonesia, were analyzed using Partial Least Squares (PLS). While HRM practices did not directly influence well-being, they significantly impacted job crafting. Interestingly, job crafting, not work engagement, emerged as a strong mediator between HRM practices and employee well-being. These findings suggest that employee-oriented HRM practices promoting autonomy (e.g., flexible work arrangements) empower hotel staff to personalize their work, ultimately leading to greater well-being. The study challenges the traditional view of work engagement as the sole mediator and highlights the under-explored role of job crafting in this context. Future research should explore the influence of individual differences and organizational culture on this complex relationship.